2008
DOI: 10.3346/jkms.2008.23.3.526
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Anaphylaxis to Chlorhexidine during Digital Rectal Examination

Abstract: Chlorhexidine is widely used as an antiseptic and disinfectant in medical and non-medical environments. Although the sensitization rate seems to be low, its ubiquitous use raises the possibility of sensitization in many patients and medical care workers. We describe a patient with anaphylaxis during digital rectal examination with chlorhexidine jelly. Urticaria, angioedema, dyspnea, and hypotension developed within a few minutes of the rectal examination. The patient fully recovered after treatment with epinep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…This increase in chlorhexidine exposure has led to potential allergic sensitization of a majority of our patients, causing a full spectrum of adverse reactions ranging from contact dermatitis and generalized urticaria to anaphylactic shock [16] . Although there have been several reports in recent years about these adverse reactions to chlorhexidine, the majority of these were isolated case reports on HCW or on patients admitted for elective procedures [1,2,[7][8][9][10][11][12][13][14]16] . To our knowledge, this is the first report on chlorhexidine anaphylactic shock masquerading as septic shock from necrotising fasciitis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This increase in chlorhexidine exposure has led to potential allergic sensitization of a majority of our patients, causing a full spectrum of adverse reactions ranging from contact dermatitis and generalized urticaria to anaphylactic shock [16] . Although there have been several reports in recent years about these adverse reactions to chlorhexidine, the majority of these were isolated case reports on HCW or on patients admitted for elective procedures [1,2,[7][8][9][10][11][12][13][14]16] . To our knowledge, this is the first report on chlorhexidine anaphylactic shock masquerading as septic shock from necrotising fasciitis.…”
Section: Discussionmentioning
confidence: 99%
“…Anaphylactic shock due to chlorhexidine has been reported after exposure to chlorhexidine via several routes such as direct contact with the skin or mucous membranes from chlorhexidine gargle, skin antisepsis lotion, lubricants or chlorhexidine-coated vascular and urinary catheters [1,2,[7][8][9][10][11][12][13][14]16] . In 2008, Bae et al [8] reported chlorhexidine anaphylaxis after digital rectal examination using chlorhexidine as a local rectal disinfectant; it was initially contributed to a latex allergy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary therapies, including topically or systemically administered anti-infective agents such as chlorhexidine, povidone-iodine, silver-coated antimicrobial dressings, and antibiotics, are limited in their efficacy and necessitate a new paradigm for treating biofilms (2,3,8,46,48). Pseudomonas aeruginosa and multidrug-resistant organisms (MDROs) such as Acinetobacter baumannii and methicillin-resistant Staphylococcus aureus (MRSA) represent a serious problem in hospitals due to nosocomial transmission and the difficulty in treating these infections with contemporary therapies (1,19,35).…”
mentioning
confidence: 99%